Description of the first five larval stages of Plesionika narval (Fabricius, 1787) (Crustacea, Decapoda, Pandalidae) obtained under laboratory conditions - Landeira, José María; Lozano-Soldevilla, Fernando; González-Gordillo, Juan Ignacio (Zootaxa, 2009)
The first five zoeal stages of Plesionika narval were obtained from 15 days of laboratory culture. All larval stages are described and illustrated in detail. Zoeal characters are compared with the previous described larvae of Plesionika acanthonotus and Plesionika edwardsii and with undetermined zoeas of Pandalidae from plankton samples.